The efforts of the Algerian authority to recover agricultural land from the settlers (1962-1995) - Balaqoun, Muhammad Al-Saleh (The Algerian Historical Journal, 2026)
This research aims to present the efforts of the Algerian authority to recover the agricultural lands that the French occupation administration seized and transferred to the property of the domain leaders and settlers and settlers, and to determine the extent to which the results of those efforts were achieved within the real estate policy during the socialist phase and the economic reforms coincided with it until the actual adoption of the new economic system. The researcher concluded that the Algerian authority, with the purpose of its actual embodiment of national sovereignty –during the historical period of study- has lifted from its historical obligation through its intervention in the enactment laws and regulations and implementing them with judicial work, has succeeded in achieving the legislative goal adopted to recover agricultural lands from the settlers.